Cerebrospinal fluid to brain transport of manganese in a non-human primate revealed by MRI - Bock, Nicholas A. (2008)
Manganese overexposure in non-human primates and humans causes a neurodegenerative disorder called manganism thought to be related to an accumulation of the metal in the basal ganglia. Here, we assess changes in the concentration of manganese in regions of the brain of a non-human primate (the common marmoset, Callithrix jacchus) following four systemic injections of 30 mg/kg MnCl2 H2O in the tail vein using T1-weighted magnetic resonance imaging (MRI) and compare these to changes in the rat following the same exposure route and dose. The doses were spaced 48 h apart and we imaged the animals 48 h after the final dose. We find that marmosets have significantly larger T1-weighted image enhancements in regions of the brain compared to rats, notably in the basal ganglia and the visual cortex. To confirm this difference across species reflects actual differences in manganese concentrations and not variations in the MRI properties of manganese, we measured the longitudinal relaxivity of manganese (χ1) in the in vivo brain and found no significant species' difference. The high manganese uptake in the marmoset basal ganglia and visual cortex can be explained by CSF-brain transport from the large lateral ventricles and we confirm this route of uptake with time-course MRI during a tail-vein infusion of manganese. There is also high uptake in the substructures of the hippocampus that are adjacent to the ventricles. The large manganese accumulation in these structures on overexposure may be common to all primates, including humans